The Research on Software Resource Re-sharing for Small and Medium-sized Enterprise Cloud Manufacturing System - Xilong Qu; Wang Yingjun (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The background, significance and the related research at home and abroad of software resource re-sharing in cloud manufacturing system are introduced. The current use and system structure of software in manufacturing are analyzed, and they are Web-based, software directly sharing, based package to share software indirectly and server-based technology for common software across the internet remote sharing. The special requirements for software sharing of cloud manufacturing system are presented.  According to the feature of small and medium-sized enterprise, a re-sharing approach of cloud manufacturing software sharing scheme for small and medium-sized enterprise is proposed, and this approach is very compatible, extended, and low-cost, it is very suitable for the manufacturing cloud of small and medium-sized enterprise. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.2918